Non-Tariff Barriers to Trade Caused by SPS Measures and Customs Procedures with Product Quality Changes - Lan Liu (Journal of Agricultural and Resource Economics, 2009)
This study develops a methodology to quantify the combined effects of two major nontariff barriers (NTBs), sanitary and phytosanitary (SPS) measures and customs and administrative procedures. We employ a constant elasticity of substitution (CES) utility function with factor-augmenting technical progress to incorporate changes in the quality of goods. We then estimate the effects of these two NTBs in the Japanese cut flower market. Results show that estimates of SPS are biased without considering product quality changes caused by the customs and administrative procedures for highly perishable agricultural products. If these Japanese NTBs were removed, findings suggest there would be a significant increase in cut flower imports by Japan.